A missing link? Network analysis as an empirical approach for critical physical geography. (19th May 2022) - Chignell, Stephen M.
Abstract: Critical physical geography (CPG) calls for integrative research on material landscapes and the socio‐political dynamics of scientific knowledge production. Network analysis, a rich tradition of tools and approaches for analyzing relational information, has seen little use in the CPG literature to date. This represents a fruitful opportunity, as many of CPG's core interests—knowledge politics, histories of scientific concepts, and ecosocial relations—can be effectively analyzed using network techniques. In this article, I argue for adapting network approaches to CPG. First, I provide an overview of various network concepts, approaches, and their origins. I then discuss bibliometric network techniques for "science mapping" including co‐word, co‐authorship, and citation analyses. Next, I describe discourse network analysis, a recent mixed‐method approach from political science. Finally, I discuss overlaps with emerging approaches from qualitative and visual network analysis. In each section, I provide existing and hypothetical examples, as well as software and visualization techniques, that demonstrate how network approaches could add new insights to CPG and related scholarship. Linking CPG with the diverse traditions of network analysis has the potential to produce new empirical understandings and bring the field into conversation with a growing body of research that spans the social sciences, natural sciences, and humanities . Key Messages: Methods and concepts from network analysis can provide valuable empirics and novel insights for critical physical geography and related fields. Network approaches can help to bridge human‐physical and qualitative‐quantitative divides in geographical research. Critical physical geographers and network scholars have much to gain from collaboration. Un lien manquant? L'analyse de réseau comme approche empirique à utiliser pour la géographie physique critique: La géographie physique critique revendique une approche de recherche intégrée traitant des paysages matériels et des dynamiques sociopolitiques de production de connaissances scientifiques. L'analyse de réseau, une riche tradition d'outils et d'approches pour l'analyse de l'information relationnelle, a été peu utilisée pour les études dans ce domaine, jusqu'à présent. Il s'agit pourtant d'une opportunité prometteuse, car de nombreux éléments fondamentaux de la géographie physique critique, comme l'histoire des concepts scientifiques, peuvent être analysés efficacement à l'aide des techniques de réseau. Dans cet article, nous plaidons en faveur de l'adaptation des approches de réseau à la géographie physique critique. Tout d'abord, nous présentons un aperçu des différents concepts et approches de réseau et de leurs origines. Nous abordons ensuite les techniques de réseaux bibliométriques pour la « cartographie scientifique ». Ensuite, nous décrivons l'analyse des réseaux de discours, une approche récente à méthodes mixtes issue des sciences politiques. Finalement, nous discutons des chevauchements avec les approches émergentes de l'analyse qualitative et visuelle des réseaux. Dans chaque section, des exemples existants et hypothétiques sont présentés, ainsi que des logiciels et des techniques de visualisation. L'établissement d'un lien entre ce domaine et les diverses traditions de l'analyse des réseaux pourrait permettre de produire de nouvelles données empiriques et de les croiser avec un grand nombre de recherches en sciences humaines ou naturelles .